The effect of short-form video addiction on undergraduates’ academic procrastination: a moderated mediation model - Xie, Jin; Xu, Xinyu; Zhang, Yamei; Tan, Yuxin; Wu, Dazhou; Shi, Mingjian; Huang, Hai (Frontiers in Psychology, 2023)
Background Short-form videos have become one of the most popular ways for people to entertain and relax. However, the intense interest in short-form videos has given rise to short-video addiction, which poses risks to both physical and mental health of individuals. Undergraduates are one of the important users for short-form videos, and the influence of short-form video addiction calls for more attention. This study aimed to investigate the association between short-form video addiction and academic procrastination among undergraduates, exploring the role of executive functions (i.e., attentional control) and personality traits (i.e., boredom proneness) in the association. Methods Using stratified random cluster sampling method, the data of 1,047 college students were used in the study. All variables were measured by empirical instruments, and all instruments were highly reliable. Mediation and moderation analysis was conducted using Model 4 and 7 in PROCESS macro powered by SPSS. Results Results revealed that short-form video addiction not only directly impacted academic procrastination but also placed indirect effect on academic procrastination through attentional control. Furthermore, the mediating effect of attentional control was contingent upon individuals’ boredom proneness. Higher levels of boredom proneness weakened the impact of short-form video addiction on attentional control. Conclusion The findings expand our knowledge of the negative effects of short-form video addiction and the underlying mechanisms, providing implications for mitigating undergraduates’ academic procrastination.